OPTIMIZATION OF EXPRESSION CONDITIONS OF GENE ENCODING ANTIGEN M OF PRRSV IN LEAVES OF NICOTIANA BENTHAMIANA BY AGROINFILTRATION METHOD - Minh Hang, Nguyen Thi; Thuong, Ho Thi; Giang, Nguyen Thu; Ngoc, Pham Bich; Nam, Nguyen Trung; Ha, Chu Hoang (Vietnam Journal of Biotechnology, 2018)
Reproductive disorders and respiratory swine (Porcine Reproductive and Respiratory Syndrome - PRRS) is an infectious disease caused by the PRRS virus (PRRSV), spread fast speeds, causing mass death when infected pigs. M protein is one of the major structural protein of the PRRSV, has a molecular weight of about 19 kDa, encoded by the open reading frame 6 (ORF6), which is used to design a subunit vaccine against back PRRSV. In this study, conditions for transient expression of the gene encoded the M protein of PRRSV in leaves of the Nicotiana benthamiana by agroinfiltration method were determined. The results show that optimal conditions for transient expression of protein M in the leaf are used the simultaneous of the A. tumefaciens strain containing vector carrying the gene encoding the protein M and A. tumefaciens containing vector carrying gene encoding supported protein HC-Pro PVY, concentration of acetosyringone with 450 µM, the bacterial cell density used to infect into leaf with OD600 is 0.5, The physiological age of the leaf suitable for infecting bacteria was young leaf and mature leaf of tobacco plants 4 to 6 weeks of age, and the transient expression time of gene encoding protein M of PRRSV in tobacco leaves is most effective 6 days after infecting. This agroinfiltration method can be used to express large amounts of protein - antigen M of PRRSV in tobacco plants to produce vaccines against this virus.